Uczeń dyslektyczny: czy nauczyciele są na niego przygotowani - Siek-Piskozub, Teresa (Neofilolog, 2011)
The present paper deals with the problem of teaching dyslexic learners in EFL classroom. A brief discussion about the nature of the learning prob-lems of dyslexic learners is followed by a report of a survey carried out among 26 EFL teachers of different teaching experience. The question-naire addressed such issues as contacts of the EFL teachers with learners diagnosed as dyslexic, their awareness of the problems such learners en-counter while learning another language, ways of treating dyslexic learners to enhance learning and an availability of the professional advice in that matter etc. The data show that not all of the surveyed EFL teachers feel prepared to the problems emerging from teaching dyslexic learners; some of the ways they choose to overcome the problem are controversial. Many do not know related literature. However, majority of them can rely on the assistance of a school pedagogue or psychologist. Yet, the fact that less than half of the respondents had training in teaching learners with dyslexia during their professional education, whereas at the same time they all report having dyslexic learners in their class, points to the need of introducing the topic to the professional training of foreign language teachers as an obligatory component.